Overview of measurements and current instrumentation for 1–10 nm aerosol particle number size distributions. (October 2020) - Kangasluoma, Juha; Cai, Runlong; Jiang, Jingkun; Deng, Chenjuan; Stolzenburg, Dominik; Ahonen, Lauri R.; Chan, Tommy; Fu, Yueyun; Kim, Changhyuk; Laurila, Tiia M.; Zhou, Ying; Dada, Lubna; et al.
Abstract: Interest in understanding gas-to-particle phase transformation in several disciplines such as atmospheric sciences, material synthesis, and combustion has led to the development of several distinct instruments that can measure the particle size distributions down to the sizes of large molecules and molecular clusters, at which the initial particle formation and growth takes place. These instruments, which include the condensation particle counter battery, a variety of electrical mobility spectrometers and the particle size magnifier, have been usually characterized in laboratory experiments using carefully prepared calibration aerosols. They are then applied, alone or in combination, to study the gas-to-particle transition in experiments that produce particles with a wide range of compositions and other properties. Only a few instrument intercomparisons in either laboratory or field conditions have been reported, raising the question: how accurately can the sub-10 nm particle number size distributions be measured with the currently available instrumentation? Here, we review previous studies in which sub-10 nm particle size distributions have been measured with at least two independent instruments. We present recent data from three sites that deploy the current state-of-the-art instrumentation: Hyytiälä, Beijing, and the CLOUD chamber. After discussing the status of the sub-10 nm size distribution measurements, we present a comprehensive uncertainty analysis for these methods that suggests that our present understanding on the sources of uncertainties quite well captures the observed deviations between different instruments in the size distribution measurements. Finally, based on present understanding of the characteristics of a number of systems in which gas-to-particle conversion takes place, and of the instrumental limitations, we suggest guidelines for selecting suitable instruments for various applications. Highlights: Previous sub-10 nm particle size distribution measurements are reviewed, and new data from three sites are presented. The presented uncertainty analysis captures the deviations in the observation data. Broad guidelines for instrument selections and future work for improving sub-10 nm measurement accuracy are provided.